2018
DOI: 10.1186/s12943-018-0832-y
|View full text |Cite
|
Sign up to set email alerts
|

Favorable outcome of patients with lung adenocarcinoma harboring POLE mutations and expressing high PD-L1

Abstract: Mutations in polymerase ε (POLE) confer favorable prognosis and outcomes in various cancer types, but their role in non-small cell lung cancer (NSCLC) is unknown. Utilizing the data of 513 patients with adenocarcinoma (LUAD) and 497 patients with squamous cell carcinoma (LUSC) from The Cancer Genome Atlas (TCGA) cohort, we tested the prognostic value of POLE mutations and programmed cell death ligand 1 (PD-L1) expression in the two main subtypes of NSCLC. POLE mutation is a favorable biomarker for the improved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 11 publications
1
23
0
3
Order By: Relevance
“…Although multiple studies have observed a better prognosis in MSI-H patients, we showed that TMB-extreme caused by dysfunctional POLE showed even better overall survival outcomes compared to TMB-high (MSI-H). Similar to our result, studies have reported that mutations in POLE proofreading domain are associated with improved prognosis in several cancer types, including high-grade glioma 33 , lung adenocarcinoma 34 , endometrial cancer, and colorectal cancer 35 . This suggests that TMB-extreme might be another promising biomarker to predict patient prognosis or guide cancer treatment.…”
Section: Discussionsupporting
confidence: 92%
“…Although multiple studies have observed a better prognosis in MSI-H patients, we showed that TMB-extreme caused by dysfunctional POLE showed even better overall survival outcomes compared to TMB-high (MSI-H). Similar to our result, studies have reported that mutations in POLE proofreading domain are associated with improved prognosis in several cancer types, including high-grade glioma 33 , lung adenocarcinoma 34 , endometrial cancer, and colorectal cancer 35 . This suggests that TMB-extreme might be another promising biomarker to predict patient prognosis or guide cancer treatment.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, blocking the PD-1/PD-L1 axis is critical for cancer immunotherapy. However, the response rates to PD-1/PD-L1 immune checkpoint blockade therapy are likely to vary widely, ∼10-20% across whole tumor types (12,13). It is urgent to find predictive molecules and relevant pathways for PD-1/PD-L1 checkpoint blockade immunotherapy to develop innovative treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, in POLE mutated lung adenocarcinomas the median TMB was increased by 1.6-fold per Mb (p = 0.026), and both PD-L1 expression and CD8+ tumor infiltrating lymphocytes were higher in this subgroup of NSCLC patients, suggesting POLE mutation as a candidate biomarker to predict the response to immunotherapy [127]. In parallel, Liu et al [128] investigated a cohort of 513 patients with lung adenocarcinoma and 497 with squamous cell carcinoma from The Cancer Genome Atlas (TCGA) to test the prognostic value of POLE mutations and PD-L1 expression. Of patient cohorts, 6% and 5.6% were positive for a POLE mutation in adenocarcinoma and squamous cell carcinoma, respectively.…”
Section: Pole Mutationsmentioning
confidence: 87%
“…POLE mutations have been identified in 7-12% of endometrial and 1-2% of colorectal cancers as well as in other tumors [125,126], including NSCLC [127,128]. Interestingly, endometrial cancers with somatic POLE proofreading domain mutations have an outstanding prognosis, which probably depends on the abundance of antigenic neoepitopes, able to stimulate a strong antitumor immune response [125].…”
Section: Pole Mutationsmentioning
confidence: 99%